A senior citizen's journey of happiness - Hashim Abdul Wahab ([Bandar Baru Bangi, Selangor] : [publisher not identified], 2014)
A senior citizen shares his experiences in achieving happiness through wellness, intellectual, environmental and friendship journeys.
Koleksi sumbangan Tun (Dr.) Ahmad Sarji Abdul Hamid.
Keywords: Hashim Abdul Wahab; Retirees; Happiness in old age